Does insulin resistance increase thyroid volume in patients with polycystic ovary syndrome? - Murat Sahin; Didem Demircioglu; Ayten Oguz; Dilek Tuzun; Mehmet Akif Sarica; Elif Inanc; Kamile Gul (Archives of Endocrinology and Metabolism)
ABSTRACT Objective To investigate the effect of gonadotropin, sex hormone levels and insulin resistance (IR) on thyroid functions and thyroid volume (TV) in polycystic ovary syndrome (PCOS). Subjects and methods 69 new diagnosed PCOS patients (age 24.82 ± 6.17) and 56 healthy control female (age 26.69 ± 5.25) were involved to the study. Fasting plasma glucose, lipid profile, insulin, thyroid stimulating hormone (TSH), free thyroxine (fT4), estradiol (E2), luteinizing hormone (LH), follicle stimulating hormone levels and urine iodine were measured in all participants. Thyroid and pelvic ultrasound were performed in all participants. Results Insulin, HOMA-IR, LH, E2 and TV were higher in PCOS group (p < 0.05). TV was significantly higher in PCOS patients with IR compared to non-IR PCOS patients (p < 0.001), while TSH, fT4, and urine iodine levels were similar between these groups (p > 0.05). There was a negative correlation between E2 and TSH (p < 0.05) and a positive correlation between TSH and TV (p < 0.05). There was a significant positive correlation between TV and LH, insulin, HOMA-IR (p < 0.05). Conclusion This study showed that TV was increased in patients with insulin resistance but differences in TSH and LH levels may affect TV changes as well.